Lessons for the future: Reflections on a review of child death overview panels through a local lens in the United Kingdom. (June 2020) - Sanders, Caroline; Fisher-Smith, Debbie; Neill, Sarah; Jones, Margaret
Child death overview panels (CDOPs) were set up in the United Kingdom following the confidential enquiry into maternal and child health. Their scope is to identify learning points and modifiable factors that focus on improving services and prevent further deaths. In the light of UK national review and subsequent legislative changes to local safeguarding arrangements, we wanted to share the lessons learnt from our local network study during this time of transition. At times of system change, organizational memory can be eroded, which results in lost opportunities to further strengthen multi-agency working in practice. Overall, our local study highlighted key learning points which could be of use in emergent safeguarding partnerships. Professionals need to continue to actively pursue and create opportunities to collect and collate comprehensive data and promote collaborative multi-agency arrangements. Panels need to be responsive to all partners involved in the safeguarding process, which includes parents. A level of reciprocity needs to be nurtured for safeguarding panel members and acute care providers to work in ways which promote learning, consider emotional support systems and explore ways to define and mobilize knowledge that can inform the safeguarding process and prevent future avoidable child deaths.